2017
DOI: 10.1080/02713683.2017.1302590
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy of an Injectable Microsphere-Hydrogel Ocular Drug Delivery System

Abstract: The current study demonstrates that the DDS can effectively decrease laser-induced CNV lesions in a murine model. Controlled and extended release from our DDS achieved greater treatment efficacy using an order of magnitude less drug than what is required with bolus administration. This suggests that our DDS may provide a significant advantage in the treatment of posterior segment eye diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 36 publications
2
47
0
1
Order By: Relevance
“…By embedding anti-VEGF filled PLGA microspheres in a thermo-responsive PNIPAAm-PEG-diacrylate hydrogel, Osswald et al were able to achieve a sustained release of Ranibizumab (Lucentis™) and Aflibercept (Eylea™) for almost 200 days in vitro [105]. Bioactivity of the anti-VEGF agents was also retained as evidenced by the significantly smaller CNV lesion areas in the treated CNV rat models of the study [99].…”
Section: Hydrogels For Sustained Delivery Of Anti-vegfmentioning
confidence: 97%
See 1 more Smart Citation
“…By embedding anti-VEGF filled PLGA microspheres in a thermo-responsive PNIPAAm-PEG-diacrylate hydrogel, Osswald et al were able to achieve a sustained release of Ranibizumab (Lucentis™) and Aflibercept (Eylea™) for almost 200 days in vitro [105]. Bioactivity of the anti-VEGF agents was also retained as evidenced by the significantly smaller CNV lesion areas in the treated CNV rat models of the study [99].…”
Section: Hydrogels For Sustained Delivery Of Anti-vegfmentioning
confidence: 97%
“…Most hydrogel platforms have not only shown to be biocompatible but also allow a sustained release of bioactive anti-VEGF to the retina for durations of multiple months [91,92,[98][99][100][101][102] (Table 2). Yu et al developed a hydrogel system comprised of natural polymers.…”
Section: Hydrogels For Sustained Delivery Of Anti-vegfmentioning
confidence: 99%
“…They are also useful for circumventing the need for frequent repeat injections—which presents several risks and complications to patients—by acting as a drug depot even for unstable protein molecules [ 140 ]. There are a number of in-situ gelling systems reported for ocular delivery of proteins [ 225 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 ]. Xue et al [ 305 ] developed thermosensitive gels of anti-VEGF drugs (bevacizumab and aflibercept) using a PEG-polypropylene glycol (PPG)-PCL multiblock copolymer (hydrophilic–hydrophobic biodegradable copolymer) [ 305 ].…”
Section: Polypeptide Deliverymentioning
confidence: 99%
“…This type of thermosensitive hydrogel has been widely investigated for various biomedical applications (e.g., drug delivery, wound healing, tissue engineering) . A recent study reported a controlled and extended release of anti‐VEGFs from PNIPAM‐thermosensitive hydrogel to effectively treat laser‐induced choroidal neovascularization . Following a single intravitreal injection, PNIPAM thermosensitive hydrogel is regarded as safe, biocompatible, and well tolerated with no long‐term adverse system effects during a 12‐week study.…”
Section: Ophthalmic Hydrogel Systemmentioning
confidence: 99%